Epistemologi Pendidikan Agama Islam dalam Paradigma Baru: Studi Kualitatif tentang Integrasi PAI dan Ilmu Kejuruan di SMK Wira Informatika Global Parungkuda - Ahmad Salim; Mulyawan Safwandy Nugraha (JIP: Jurnal Ilmu Pendidikan, 2026)
The development of technology-based vocational education requires Islamic Religious Education (IRE) to adapt in order to remain relevant to students’ needs. This study aims to analyze the epistemology of IRE within a new paradigm and to examine the integration of IRE with vocational subjects at SMK Wira Informatika Global Parungkuda. This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews, classroom observations, and document analysis, and were analyzed thematically using source triangulation. The findings indicate that IRE epistemology is understood in an integrative manner, positioning revelation as the primary normative source while being interpreted through reason and contextualized by students’ vocational experiences. The integration of IRE and vocational knowledge is manifested through the linkage of Islamic values with digital ethics and professional conduct. This study concludes that IRE functions as a value framework guiding character formation and competency development in technology-based vocational education.